Engineering Nt.BtsCI and Nb.BtsCI nicking enzymes and applications in generating long overhangs - Too, Priscilla Hiu-Mei (Oxford University Press, 2010)
Type IIS restriction endonuclease BtsCI (GGATG 2/0) is a neoschizomer of FokI (GGATG 9/13) and cleaves closer to the recognition sequence. Although M.BtsCI shows 62% amino acid sequence identity to M.FokI, BtsCI and FokI restriction endonucleases do not share significant amino acid sequence similarity. BtsCI belongs to a group of Type IIS restriction endonucleases, BsmI, Mva1269I and BsrI, that carry two different catalytic sites in a single polypeptide. By inactivating one of the catalytic sites through mutagenesis, we have generated nicking variants of BtsCI that specifically nick the bottom-strand or the top-strand of the target site. By treating target DNA sequentially with the appropriate combinations of FokI and BtsCI nicking variants, we are able to generate long overhangs suitable for fluorescent labeling through end-filling or other techniques based on annealing of complementary DNA sequences.